About Possibility of Remote Diagnostics of the Respiratory System by Auscultation - E. G. Zaitseva; M. V. Chernetsky; N. A. Shevel (Приборы и методы измерений)
Development of technical base, software, accumulated information on the diagnosis of the respiratory system provided the prerequisites for creating remote diagnostics of the human respiratory system through auscultation. The known methods do not solve the problem of determining auscultation points at patent´s housing without a diagnostic specialist. The purpose of this study is to develop a method for remote diagnostics of the respiratory system which provides ability to determine the points of auscultation without presence of a diagnostic specialist.The definition of auscultation points is provided using a computer program that allows to calculate the points´ coordinates based on the coordinates of points that determine the anatomical structure of the patient's torso. The patient or his assistant places the recording device at the auscultation points combining their images on the display with the image of the location of the recording device. The signal recorded at the auscultation point is remotely transmitted to a specialist for direct analysis and/or computer processing. The diagnostic module consists of two main units. The first unit contains a stethoscope, microphone, and amplifier connected to a mobile phone or other similar device containing an accelerometer. The patient or his assistant at the housing uses the unit. The second unit is a mobile phone with a mechanical marker or a computer with the ability to access the network in conjunction with the necessary software and is used remotely by a diagnostic specialist. The layout of the unit for recording and transmitting breath sounds was made. To avoid discrepancies in the diagnostic results the technical characteristics of the module elements must be normalized. Unified software is required for the module to function. The organizational tasks that need to be solved for the implementation of diagnostics are formulated.Use of the method of remote diagnostics of the respiratory system, providing the ability to determine points of auscultation without the direct presence of a diagnostic specialist and the module will allow increasing efficiency of treatment of pulmonary diseases reduce infection risks and economic costs.